Early-Life Stress, HPA Axis Adaptation, and Mechanisms Contributing to Later Health Outcomes - Maniam, Jayanthi; Antoniadis, Christopher; Morris, Margaret J. (Frontiers in Endocrinology, 2014)
Stress activates the hypothalamic-pituitary-adrenal (HPA) axis, which then modulates the degree of adaptation and response to a later stressor. It is known that early life stress can impact on later health but less is known about how early life stress impairs HPA axis activity, contributing to maladaptation of the stress response system. Early life stress exposure (either prenatally or in the early postnatal period) can impact developmental pathways resulting in lasting structural and regulatory changes that predispose to adulthood disease. Epidemiological, clinical and experimental studies have demonstrated that early life stress produces long-term hyper responsiveness to stress with exaggerated circulating glucocorticoids, and enhanced anxiety and depression-like behaviours. Recently, evidence has emerged on early life stress induced metabolic derangements, for example hyperinsulinemia and altered insulin sensitivity on exposure to a high energy diet later in life. This draws our attention to the contribution of later environment to disease vulnerability. Early life stress can alter the expression of genes in peripheral tissues, such as the glucocorticoid receptor and 11-beta hydroxysteroid dehydrogenase (11β-HSD1). We propose that interactions between altered HPA axis activity and liver 11β-HSD1 modulates both tissue and circulating glucocorticoid availability, with adverse metabolic consequences. This review discusses the potential mechanisms underlying early life stress induced maladaptation of the HPA axis, and its subsequent effects on energy utilisation and expenditure. The effects of positive later environments as a means of ameliorating early life stress induced health deficits, and proposed mechanisms underpinning the interaction between early life stress and subsequent detrimental environmental exposures on metabolic risk will be outlined. Limitations in current methodology linking early life stress and later health outcomes will also be addressed.